PENGARUH PENERAPAN PENDEKATAN TARL TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI TRIGONOMETRI SISWA KELAS XI: Pengaruh Penerapan Pendekatan Tarl Terhadap Hasil Belajar Matematika Pada Materi Trigonometri Siswa Kelas XI - Natasya; Karmilawati, Karmilawati; Widya Wardana, Irena; Andani, Meri; Michelangelo Repo, Francis; Astuti, Reni (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
This study aims to improve the mathematics learning outcomes of grade XI students of SMA Negeri 2 Pontianak on trigonometry material through the Teaching at the Right Level (TaRL) approach. This approach is adjusted to the level of student understanding which is categorized into three levels: basic, intermediate, and advanced. Classroom action research was conducted in two cycles with different learning models: Problem Based Learning (PBL) in cycle I and Jigsaw Cooperative in cycle II. The results showed a significant increase in student learning completeness, from 22.2% in the pre-cycle to 66.67% in cycle I, and 86.11% in cycle II. The average student score increased from 64.97 to 86.39, and student active involvement also increased from 50% to 55,56%. These findings prove that the application of the TaRL approach can significantly improve student conceptual understanding, active participation, and learning outcomes.